(untitled) (Medico Legal Update, 2020)
Background: Mental health is a major that often gets bad perception. Bad perceptions of mental health often occur in special populations (students). It is necessary to measure student perceptions to describe their perceptions regarding mental health Objective : To describe student perceptions (aspects of cognition, aspects of affection and aspects of conation) about mental health. Method: This study uses quantitative method with descriptive approach. The sample of this study are 100 college students of Public health major in UIN Alauddin, Makassar, Result: In general, cognitive aspect of respondents is positive, as well as psychomotoric and affection aspect. Conclusion : Students’ perceptions related to mental health after measurement tend to be good for all three aspects (cognition, affection and conation) without one statement having the largest negative percentage.